Integrating environmental concerns into the teaching of mathematical optimization - Fernández-Torres, María J.; Hildebrandt, Diane; Sempuga, Baraka Celestin; Caballero, José A. (Education for chemical engineers, 2020)
•How to integrate environmental concerns into Chemical Engineering education.•University education in Sustainable Development through two case studies.•Human waste can be managed to obtain energy, fertilizer and improve sanitation.•Mathematical Optimization is used in this context and explained for non-specialists. Given the damage that the natural environment suffers from human activities, it is relevant to provide ecological literacy to all Chemical Engineering students. Sometimes, this information is offered through elective courses and/or seminars and consequently it might not reach the whole class. Some courses have more obvious connections to environmental issues, while others do not appear to. In this paper, we aim to show through some solved examples how to introduce an environmental topic in the subject Mathematical Optimization. The problems goal is to decide on the best logistics for the transport and management of human waste that will be used in the production of sustainable energy. The context is that of improving the sanitation and hygiene in areas of the developing world, while simultaneously creating job opportunities within the communities. The research that we have conducted for finding the proper way to address the environmental analysis in class, led us first to the Sustainable Development Goals (SDGs), but later on, other theories such as the Cradle-to-Cradle (C2C) have proven to be more comprehensive and therefore, better. We believe that this multidisciplinary paper shows how to integrate environmental concerns and understanding in the Chemical Engineering curricula.